Pre-Trial Resolution of Administrative Disputes in Lithuania: the Problematics of Legal Interpretation - Paškevičienė, Laura (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] In this article the author analyzes the Lithuanian case law related to the pre-trial administrative disputes resolution, seeking to estimate the level of its consistency in qualifying the institutional and functional aspects of administrative dispute resolution out-of-court as the pre-trial, as described in general legal regulation. The author is trying to investigate, what rules for interpretation and what substantial arguments are used in this legal evaluation and qualification, and to assess the influence of this court jurisprudence to the formation of the pre-trial administrative dispute resolution as a legal institute, and to the implementation of the effective legal action in the protection of persons’ rights under the pre-trial means.